Harvesting of Boro Paddy in Haor Areas of Bangladesh: Interplay of Local and Migrant Labour, Mechanized Harvesters and Covid-19 Vigilance in 2020 - Md. Jahangir Kabir; Md. Shahjahan Kabir; Md Abdus Salam; Mohammad Ariful Islam; Md Imran Omar; Md. Abdur Rouf Sarkar; Mohammad Chhiddikur Rahman; Afroza Chowdhury; Md. Shajedur Rahaman; Limon Deb; Md. Abdullah Aziz; Md Abu Bakr Siddique; et al. (Bangladesh Rice Research Institute, 2020)
During countrywide lockdown due to COVID-19 pandemic wage workers from different parts of the country were encouraged to move to haor areas for harvesting Boro paddy amid risk of community transmission of the virus in late April to early May 2020. This study attempted to delineate the socioeconomic and health risk management status of migrant harvest labour and to assess the yield and prices of Boro paddy in three haor districts of Kishoreganj, Netrakona and Sunamganj. A quick and clean questionnaire survey was conducted using mobile phones to collect first hand data from 90 labour leaders and 90 Boro farmers during 4th week of April – 1st week of May 2020. Both tabular and inferential analyses were carried out in the study. Ministry of Agriculture very promptly mobilized the local administration, law enforcement agencies and health department with support from the Dept. of Agricultural Extension to make special arrangements for speedy movement of migrant labour to haor areas for harvesting Boro paddy. Trucks, engine boats and pickup vans were common transports for migrant labour. The wage workers migrated mainly from Pabna, Tangail, Sirajganj, Mymensingh, Sylhet, Manikganj and non-haor areas of Sunamganj. Most wage workers were 30 – 40 years old. The availability of migrant harvest labour was 20% higher in Sunamganj and 2% higher in Kishoreganj in the current year, compared to last year. However, their availability in Netrakona was 6% lower this year than the last year. Overall, the participation of migrant labour in harvesting Boro paddy in the last year (2019) was 74% – 80%, but it decreased to 60%– 69% this year (2020). This was due to the higher participation in harvesting of Boro paddy by local workers many of whom were actually returnees from cities due to Corona shutdown. The contributions of combine harvesters and reapers were 6%, 7% and 9% in Sunamganj, Kishoreganj and Netrakona, respectively. The cost of harvesting Boro rice by combine harvesters and reapers including the cost of carrying by labour and threshing by power thrashers was 31% – 39% lower than the cost of manual harvesting, carrying and threshing. The health risk management practices of migrant labourers included maintaining social distance from (i) dwellers of in-migration village and from each other while harvesting rice in the fields. Besides, the labourers wore masks while travelling by vehicles, walking out to fields for harvesting rice and going to market places for buying essentials. However, they could not comply social distancing properly in their places of accommodation. Besides, they could not wear masks always while harvesting rice because of hot humid weather and they could not wash hands frequently because of the unavailability of water in the fields. The average yields of wet paddy were 54 – 60 mounds/acre for BRRI dhan28, 64 – 67 mounds/acre for BRRI dhan29, and 70 – 72 mounds/acre for hybrids. These yields were 69% – 82%, 20% – 33% and 20% – 30% higher in 2020 than in 2019, respectively, due to very favourable weather conditions. Similarly, the average market price of wet Boro paddy was BDT 706 – 783/mound in April 2020, which was 20%-30% higher than in April 2019. However, the current price of Boro paddy was 20% – 30% lower than the farmers' expected price this year. Thus, the procurement of Boro paddy at the declared minimum price of BDT 26/kg needs to be implemented at full scale during the harvesting period so that farmers' incentives to produce rice is sustained. In future, more harvesting machines will be required in haor areas for timely harvesting of Boro paddy.
Keywords: 330; COVID-19; Mechanization; Haor; Rice; Harvest; Bangladesh